Sanitary treatment of gas emissions from ammonia in the production of soda ash - Склабинский, Всеволод Иванович; Аль Хайят Мохаммед, Надим Касим (Technology audit and production reserves, 2014)
The research results of the effectiveness of the spray vortex countercurrent mass transfer apparatus in the absorption of ammonia are given. The main sources of ammonia emissions in the production of soda ash and disadvantages of existing industrial units are determined. The analysis of structural mass transfer equipment, which appears in recent years, allows to identify one of the areas of mass transfer technology - the spray apparatus with high degree of turbulence. High velocity of gas (steam) also allows to atomize of liquid droplets of small size and to accelerate the process by increasing the interfacial mass transfer surface. It is developed and proposed the modernized sanitary washing apparatus for process gases. It is shown that the minimum entrainment in fluid vortex devices have a spray liquid specific design. The value of entrainment after vortex devices is much smaller than the entrainment after bubbling plates. The entrainment reducing will increase the driving force for mass transfer process, and increase the absorption of the gaseous ammonia. The operation of the upgraded unit for sanitary flushing process gases is researched and graph of the characteristics of the device is shown. The research results of the absorber of sanitary cleaning of gaseous ammonia have shown that it operates stably in a wide range of loads on the machine phases. The effectiveness of the new device is significantly higher than the efficiency of the existing enterprise sanitary washer. The efficiency is rather high vortex apparatus and reaches more than 99 % in the entire range of each of the factors.